P-184 New approaches to volunteering – learning from europe?. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Scott, Ros
Abstract : Introduction: Volunteering in hospice and palliative care in recent years has been in the spotlight as services consider the vital role that volunteers can play in helping services to meet the growing and changing demands on their services. As society changes so too does volunteering as prospective volunteers have different expectations and increasing demands on their time. This has been a focus of the work of the European Association for Palliative Care (EAPC) Task Force on Volunteering as it seeks to explore the roles, understanding, constructs and frameworks for volunteering in hospice and palliative care (HPC) in different countries throughout Europe. Approach: Drawing on early outcomes from the work of the Task Force this session will explore what learning there might be for the UK from the perspective of the: Changing nature of volunteering in different countries Challenges facing volunteering in hospice and palliative care and responses to these Different perceptions of HPC volunteering Approaches to frameworks and training This session will also consider how the UK might address some of these areas, including the 'place' of volunteers within the multi-disciplinary team and the importance of this to the quality of care for patients and families. Conclusion: As both hospice and palliative care and volunteering continue to develop, the changes in each have the potential to significantly influence the other. If we are to successfully meet the complex and changing needs of patients and their families volunteers must surely be considered as part of the package of care and support. Exploring practice and learning from other countries can challenge our thinking and give us new ideas for creative and innovative approaches to maximise the future contributions of volunteers for the benefit of those we support.